O FUNDEB e a municipalização do ensino fundamental em São Paulo, novo fundo, velhas tendências - Silvio Cesar Nunes Militão (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This article aims to analyze how the process of elementary school municipalization, which has been introduced in the middle 90's, has worked in the current FUNDEB context. Anticipated and favored by the state government decisions, and strongly induced by the substituted FUNDEF, the process history and enfoldments have initially been recuperated by means of bibliographical and documental analysis. The text demonstrates that the process of elementary school municipalization is still in course in São Paulo state, in spite of the new FUNDEB, the financial system applied to support the entire basic education degree. Although it represents a significant advance comparing to the previous one, the new Fund has also induced elementary school municipalization. The article finally reveals that even with FUNDEB, the mentioned process keeps showing the same remarkable trends observed under the previous Fund: (1) municipal adherence based on economic approach; (2) municipal authorities' preference for the first years of elementary school; (3) elementary school partitioning.